Psychological disturbance and cognitive functioning in TBI patients. Issue 6 (2nd November 2019) - Udala, Megan; Clark, Jeneya; Miller, Harry; Leitner, Damian; Libben, Maya
Abstract: The current study examined psychopathology and neuropsychological test performance in a traumatic brain injury (TBI) patient sample. Previous research has found that the Minnesota Multiphasic Personality Inventory – Second Edition (MMPI-2) indices of psychological disturbance were related to specific neuropsychological tests of attention and memory. Furthermore, higher scores on clinical scale 2 (Depression) and higher scores on the content scales of Fears and Bizarre Mentation of the MMPI-2 were related to poorer performance in, most notably, Attention and List Learning factors. The present study sought to extend the research by adding a neuropsychological measure of conceptual reasoning. A sample of 116 TBI patients referred for evaluation at a private practice clinic were administered a battery of neuropsychological measures of list learning, working memory, verbal memory, visuographic memory, and conceptual reasoning, as well as the MMPI-2 to assess emotional functioning. Regression analysis indicated that an overall model of MMPI-2 indices significantly predicted poorer performance on List Learning. More specifically, higher scores on the content scales of Obsessions and Fears were most robustly associated with poorer neuropsychological test performance for List Learning and Working Memory respectively. Findings suggest psychopathology is correlated with performance on neuropsychological measures for TBI patients.